Moderation effect of individualism/collectivism, uncertainty avoidance and long term orientation on adoption e-commerce in batam city SMEs: development of the UTAUT 2 - Widya Reza; Vitri Aprilla Handayani (Institute of Computer Science (IOCS), 2023)
Batam City MSME actors still encounter several obstacles in running their business, such as determining market share, operational costs, marketing outreach, and customer loyalty. To overcome this problem, MSME players in Batam City are required to be more creative in utilizing technology such as e-commerce. This study aims to analyze the factors that influence the adoption of e-commerce in MSMEs in Batam City using the UTAUT 2 model by considering cultural factors. The data used in this study is primary data obtained through a survey of Batam City SMEs using a questionnaire with a purposive sampling method. The sample used was 250 MSME actors. The analytical method used in this study is Structural Equation Modeling (SEM). Based on the results of the analysis, it was found that facilitating conditions, habits, and behavioral intentions directly affect the use behavior variable. Cultural factors of individualism/collectivism, uncertainty avoidance, and long-term orientation also managed to moderate the influence of behavioral intention variables on user behavior.